Fe3O4@SiO2 core–shell nanoparticles for biomedical purposes: adverse effects on blood cells. (12th August 2016) - Achilli, C.; Grandi, S.; Guidetti, G. F.; Ciana, A.; Tomasi, C.; Capsoni, D.; Minetti, G.
Abstract : Magnetite nanoparticles coated with silica, obtained by a sol–gel process in the reverse micelle microemulsion, were characterized and homogeneously suspended in water in order to assay their biocompatibility toward blood cells, in view of a potential medical use of this material. Abstract : Magnetite nanoparticles coated with silica, obtained by a sol–gel process in the reverse micelle microemulsion, were characterized and homogeneously suspended in water in order to assay their biocompatibility toward blood cells, in view of a potential medical use of this material. Their hemolytic, pro-thrombotic and pro-inflammatory properties were observed.